Pengembangan Media Roda Putar Pada Penerapan Model Teams Games Tournament Untuk Meningkatkan Hasil Belajar Mata Pelajaran IPAS Kelas IV SD - Qorina, Najla; Fakhriyah, Fina; Siti Masfuah (LPPM Institut Pendidikan Nusantara Global, 2025)
Limitations in the use of learning media in schools and teaching methods that tend to be monotonous are one of the main factors in low student learning outcomes. This study aims to develop innovative learning media in the form of a rotating wheel based on the Teams Games Tournament (TGT) learning model to improve student learning outcomes in the subject (IPAS), especially in the material on natural phenomena and economic activities in grade IV of Elementary School. The research method applied is Research and Development (RnD) by adapting the ADDIE development model which includes five stages, namely analysis, design, development, implementation, and evaluation. Data collection was carried out through questionnaires, tests, interviews, observations, and documentation, while data analysis techniques used qualitative and quantitative descriptive approaches. The results of the study showed that the developed rotating wheel learning media was able to improve student learning outcomes. This was proven through the normality test and t-test which showed a significance value of more than 0.05 for both data, namely pretest (0.410) and posttest (0.067) which means the data is normally distributed. Meanwhile, the t-test results showed a significance value of 0.001, which indicated a significant difference between the pretest and posttest values.